2016
DOI: 10.24198/pjd.vol28no2.13718
|View full text |Cite
|
Sign up to set email alerts
|

Exposure time of virgin coconut oil against oral Candida albicans

Abstract: Introduction: Virgin coconut oil (VCO) is an oil which is purely made as a product of the coconut palm and has been used for centuries in the culinary industry and the medical field. Currently, VCO is used widely in medical field due to its effectiveness as antibacterial, antiviral, and antifungal properties. Objective of this experimental study was to prove the effectiveness of virgin coconut oil by determining its exposure time at concentration of 25% to inhibit growth of oral Candida albicans. Method: The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…One of the purest forms of coconut oil is VCO. Several reports suggested that VCO has antifungal, antibacterial, antiviral and antioxidant properties [17]. VCO has antimicrobial activity against Candida albicans, Staphylococcus aureus, Streptococcus mutans, Actinomyces spp., Prevotella spp.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the purest forms of coconut oil is VCO. Several reports suggested that VCO has antifungal, antibacterial, antiviral and antioxidant properties [17]. VCO has antimicrobial activity against Candida albicans, Staphylococcus aureus, Streptococcus mutans, Actinomyces spp., Prevotella spp.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of extract exposure to C. albicans was 24 h [10]. VCO has many medical effects due to the high percentage of medium chain fatty acids (MCFA) [10,17]. Several fatty acids have the highest antifungal activities, such as lauric acid, capric acid, monoglyceride monolaurin and monocaprin [8,10,17,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations